Damage identification during an impact event using the Hilbert-Huang transform of decomposed propagation modes. (15th May 2023) - Cuomo, Stefano; Boccaccio, Marco; Meo, Michele
Abstract: This work proposes a novel baseline-free method for real-time structural damage diagnosis during low-and high-velocity impact, based on the decomposition of the propagating modes caused by impact events. The high-frequency components (extensional) and the medium–low frequency components (flexural) of the measured waves are separated via Hilbert-Huang transform (HHT) through the intrinsic mode function (IMF), to obtain the amplitude and phase of the two extensional and flexural propagation modes. The Energy Ratio Ξ defined as the ratio between the maximum instant energy of the extensional mode and the maximum instant energy of the flexural mode is proposed. Results show that values of Ξ between 0 and 1 are a sign of low probability of damage during impact. When the Ξ parameter is reaching values higher than 1, penetration and perforation of the structure is likely to occur, since the extensional component in this scenario is more dominant than the flexural one. Tests were conducted on aluminium and CFRP samples with simple and complex geometries, subjected to low- and high-velocity impacts (with and without perforation) to validate the flexibility of the proposed method. Experimental results have demonstrated the effectiveness of the technique to discern elastic and damaging impact on different sample geometries and at different impact velocities in real-time and without the requirement of baseline datasets.